2019
DOI: 10.1016/j.abd.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an instrument to assess the knowledge of general practitioners and pediatricians about photoprotection and solar radiation

Abstract: BackgroundThe knowledge of general practitioners about photoprotection is unknown.ObjectivesTo develop and validate an instrument to evaluate the knowledge of general practitioners and pediatricians about photoprotection, gauging the knowledge of these professionals.MethodsThe study followed the steps: (1) Literature identification and item elaboration related to the theme; (2) Content validation; (3) Apparent validation; (4) Construct validation: internal consistency analysis and discriminatory analysis; (5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…[28][29][30] Additionally, males scored lower levels of photoprotection knowledge and reported using sunscreen less compared to females, which may be related to the higher incidence of skin cancer in males. 3,5 In contrast, female participants were more likely to use all types of photoprotective measures, including wearing hats and long-sleeved clothes, using parasols, and applying sunscreen.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…[28][29][30] Additionally, males scored lower levels of photoprotection knowledge and reported using sunscreen less compared to females, which may be related to the higher incidence of skin cancer in males. 3,5 In contrast, female participants were more likely to use all types of photoprotective measures, including wearing hats and long-sleeved clothes, using parasols, and applying sunscreen.…”
Section: Discussionmentioning
confidence: 98%
“…Skin cancers, actinic keratosis, hyperpigmentation, and hypopigmentation are known to be significantly related to exposure to ultraviolet (UV) radiation. [1][2][3][4] In particular, UV radiation is known to cause genetic mutations related to tumor development in conditions such as actinic keratosis and skin cancer. 3,5 Studies have shown that these diseases are more prevalent in outdoor workers, occur more frequently in whites, and are more common in the face, an area of high exposure to sunlight.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations